De l’expérimentation à l’alternative écologique ? Le cas d’un vide-greniers en quartier populaire - Léa Billen (Développement Durable et Territoires)
The bazaar of the community organisation « Régie de quartiers de Saint-Denis » is a second-hand place located in a working-class neighbourhood. Starting from this concrete case, the article discusses the conditions allowing an ecological experimentation to become as an alternative to capitalist lifestyles. The bazaar is depicted through the lens of three objections addressed to experimentations, which question their alternative ambition : their local and punctual scope, their difficulty in mobilising the working classes, and their lack of political radicality. It shows that the bazaar overcomes the first two limits and incompletely embodies the alternative of political ecology in a working-class neighbourhood. It presents the bazaar as an ongoing ecological alternative whose political significance is unevenly claimed by the experimenters.